Here's the question you clicked on:
heathernelly
((((;
Start with the realization that this is the difference between 2 perfect squares. And when you have a^3 - b^3, this can be factored into (a - b)(a^2 + ab + b^2)
Sorry, just saw the plus sign.
It is the SUM of 2 perfect squares, which can be factored. a^3 + b^3 = (a + b)(a^2 - ab + b^2).
Google it or yahoo it . http://answers.yahoo.com/question/index?qid=20110601120209AAC6qWn
So, 27x^3 + 125 = 0 -> (3x)^3 + 5^3 = 0 and you can use my formula (second post) and you can find the first zero.
oh okaay, thank you very muchh :)
(3x)^3 + 5^3 = 0 = (3x + 5)(9x^2 - 15x + 25)
You will have one real zero at x = -5/3 and 2 imaginary zeros that come from the second factor. Just use the quadratic formula.
You are very welcome!